Microstructure and local mechanical properties of Pt-modified nickel aluminides on nickel-base superalloys after thermo-mechanical fatigue - Franke, Oliver; Durst, Karsten; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2007)
A single-phase and a two-phase platinum modified aluminide coating on the nickel-base superalloy CMSX-6 were investigated with analytical scanning electron microscopy (SEM) and nanoindentation in the as-coated condition and after thermo-mechanical fatigue loading (TMF). The microstructure of the single-phase coating exhibits high stability during TMF-loading and hardly any grain coarsening is observed. The grain size was determined by electron channelling contrast images (ECC) in the SEM to be 45.6 and 39.7 μm, respectively. In the two-phase coating the PtAl2 second phase particles dissolve throughout TMF-loading causing a coarsening of the β-NiAl grains from an original size of 5.5-18.5 μm after TMF. The microstructural evolution is associated with a strong change in the local mechanical properties as determined by nanoindentation. It is found that Young's modulus as well as hardness decrease in both investigated systems. The change in local mechanical properties is related to the microstructural and chemical changes of the coating. As far as the β-NiAl phase is concerned, the Al concentration is found to be the main reason for the decrease in Young's modulus. This behaviour was confirmed by nanoindentation measurements on a Ni-NiAl diffusion couple.
Created from Fastlane, Scopus look-up
Keywords: Hardness; Microstructure; Nanoindentation; NiAl-diffusion coatings; Thermo-mechanical fatigue; Young's modulus